2018
DOI: 10.1111/disa.12288
|View full text |Cite
|
Sign up to set email alerts
|

Effort–reward imbalance and burnout among humanitarian aid workers

Abstract: This study sought to examine stress-related working conditions-defined in terms of effort-reward imbalance (ERI)-and their association with burnout among a large, international sample of humanitarian aid workers. Descriptive statistics were applied to cross-sectional survey data (N=1,980) to profile ERI and burnout and Pearson's χ tests were used to characterise associated socio- and occupational-demographic factors. Associations between ERI and burnout were established using binary logistic regression to gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 72 publications
(98 reference statements)
1
40
0
1
Order By: Relevance
“…The upper tertile was classified as a high job strain group and the middle and lower tertiles were combined to produce a low job strain group. In accordance with previously published studies [11,12,18], social support scores were also divided into tertiles, with the lowest tertile classified as a low social support group.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…The upper tertile was classified as a high job strain group and the middle and lower tertiles were combined to produce a low job strain group. In accordance with previously published studies [11,12,18], social support scores were also divided into tertiles, with the lowest tertile classified as a low social support group.…”
Section: Methodsmentioning
confidence: 97%
“…Each regression model was adjusted for age, marital status, and pay grade. All regression models were run separately for males and females because previous humanitarian aid worker studies have shown gender differences in stress-related variables [11,12].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to routine exposure to traumatic events (Strohmeier & Scholte, 2015), humanitarian workers experience demanding working conditions, long working hours, separation from family members, interpersonal conflicts within teams, negative response from communities they serve, safety and security concerns, and financial hardship (Cardozo et al, 2013;Ehrenreich & Elliott, 2004). Therefore, apart from traumatic exposure, those work-related demands with limited organizational support were shown to contribute explicitly to the humanitarian workers' psycho-morbidity (Jachens, Houdmont, & Thomas, 2019).…”
Section: Highlightsmentioning
confidence: 99%
“…To our knowledge, two studies [15,16] have been conducted to illustrate the relationship between effort-reward imbalance and burnout, one involving global humanitarian aid workers and other involving nurses in the Netherlands. No study was found to report the relationship between effort-reward imbalance and favorability to the work environment among Chinese nurses.…”
Section: Introductionmentioning
confidence: 99%